A multimode substrate integrated waveguide based self‐hexplexing antenna for mobile terminal applications. Issue 9 (7th June 2022) - Duan, Rui; Zhang, Bing; Zhou, Yanping; Huang, Kama
Abstract: A low‐profile self‐hexplexing antenna based on the multimode substrate integrated waveguide (SIW) cavity is presented for mobile terminal applications. It has three feeding ports, each of which can generate two resonant modes. Taking the advantage of the truncated SIW resonant cavity, the footprint of the antenna remains compact in the multiple functional mode scenario. The proposed antenna operates at six different modes, namely TM10 mode at 3.55 GHz, TM01 mode at 4.85 GHz, TE110 mode at 2.45 GHz, TE220 mode at 5.6 GHz, TE110 mode at 3.4 GHz and TE120 mode at 5.35 GHz. Good agreement is achieved between the simulated and measured antenna performance. The excitation and field distribution of each mode is analyzed. Keeping the structure miniaturized, the proposed antenna realizes hex‐band characteristics without excessive feeding ports. It can be used for Microwave Access (WIMAX), the 5th Generation Mobile Communication Technology (5G) and Wireless Local Area Network (WLAN) applications, which is suitable for mobile handheld multiband terminals.